‘I’m his safe space’: Mothers’ Experiences of Physical Violence From Their Neurodivergent Children—Gender, Conflict and the Ethics of Care - Holt, Amanda (The British journal of criminology, 2024)
Drawing on recent criminological scholarship on child to parent violence (CPV), this article applies a feminist ‘ethics of care’ framework to understand how mothers of neurodivergent children understand the violence they experience from them. Examining data from in-depth interviews with 15 mothers who experience CPV, this article explores how mothers construct themselves as a ‘safe space’ through which their child can manage their distress. The tensions and emotional conflicts this produces for mothers, as well as the harms that result, are highlighted. Discussion focusses on the usefulness of understanding family violence from an ‘ethics of care’ framework, and the implications for violence prevention through broader social change.